Association of fracture type with enophthalmos and intraorbital volume correction in orbital fractures: A computed tomographic study - Anantanarayanan Parameswaran; Elavenil Panneerselvam; Bipasha Mukherjee (Indian Journal of Ophthalmology)
Purpose: To determine the influence of different types of orbital fractures on the radiographic post-treatment outcomes. Methods: The investigation was a retrospective cohort study involving CT data of all patients who underwent delayed primary or secondary surgery for orbital/zygomatico-orbital trauma between 2019 and 2021. The sample was divided into three groups 1, 2, and 3: isolated floor, floor and medial wall, and combined orbit and zygomatic complex fractures. The type of orbital fracture was the exposure, while the outcome measures were reduction in enophthalmos and intraorbital volume and linear relationship between the two variables. Data were analyzed for variance between groups and association. Statistical significance was set at < 0.05. Results: Forty-four patients (3 females and 41 males) with a mean age of 28.6 years were included in the study. Reductions in enophthalmos (P < 0.001) and intraorbital volume (P = 0.003) demonstrated significant variance between the groups. For every cubic centimeter of reduction in volume, the reduction in enophthalmos was 0.78 mm (P < 0.001) in isolated floor fractures, 0.60 mm (P = 0.013) in combined fractures involving the floor and medial walls, and 0.24 mm (P = 0.456) in combined fractures of the orbit and zygoma. Conclusion: Correction of enophthalmos strongly depends on the type of orbital fracture. There exists a significant linear relationship between enophthalmos and intraorbital volume in fractures involving the internal orbit.